Eravacycline susceptibility was impacted by genetic mutation of 30S ribosome subunits, and branched-chain amino acid transport system II carrier protein, Na/Pi cotransporter family protein in Staphylococcus aureus - Wang, Zhanwen (BMC Microbiol, 2020)
BACKGROUND: Our previous research indicated the excellent in vitro antibacterial activity of Eravacycline (Erava) and its heteroresistance frequency against clinical Staphylococcus aureus isolates. In this study, we further aimed to investigate the mechanisms of Erava resistance and heteroresistance in S. aureus. Eight parental S. aureus isolates were induced under Erava pressure in vitro and the Erava-resistant isolates were selected and identified. Then, the genetic mutations of 30S ribosomal subunits were analyzed by PCR and sequence alignment. RT-qPCR analysis were performed to compare the relative expression of eight candidate genes impacting the susceptibility of tetracycline (Tet) between the resistant or heteroresistant and parental isolates. Furthermore, the in vitro overexpression vectors of three selected candidate genes were constructed to test their impact on the heteroresistance and resistance of Erava in S. aureus. RESULTS: The MICs elevation in Erava-induced resistant S. aureus isolates were identified and the increasing MICs values of another two Tet class antibiotics, including both omadacycline (Omada) and tigecycline (Tige) were also tested. Genetic mutations in 30S ribosomal protein S10 were found frequently in Erava-derived resistant isolates. RT-qPCR analysis and the in vitro overexpression experiments indicated that USA300HOU_RS00550 (an Na/Pi cotransporter family protein) and USA300HOU_RS01625 (a branched-chain amino acid transport system II carrier protein) contributed to Erava heteroresistance in S. aureus. CONCLUSION: Genetic mutation of 30S ribosome subunits contributed to Erava resistance, and the transcriptional overexpression of USA300HOU_RS01625 and USA300HOU_RS00550 also participated in the occurrence of Erava heteroresistance in S. aureus.